2020
DOI: 10.1177/1179547620956634
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor-Related Severe Dyspnoea: Mechanisms, Characteristic Features, Differential Diagnosis and Treatment

Abstract: With a growing number of patients on ticagrelor therapy after stent implantation, we observe many cases of side effects of the drug, mostly dyspnoea and bradycardia. In our article we present 2 patients, in which the symptoms were particularly severe. Then we describe possible mechanisms of these complications, explain how to carry out differential diagnosis, discuss when to switch ticagrelor to other antiplatelet drug and finally we present the way to deal with the symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The incidence of ticagrelor-related dyspnea was the same in both patients with chronic heart failure or chronic obstructive pulmonary disease and those without these diseases [31]. Up to date, the two most plausible hypotheses explaining the potential mechanisms of ticagrelor-induced dyspnea have been debated [10,32]. In the literature, the greatest attention is paid to a structural similarity between ticagrelor and adenosine, activation of adenosine receptors (A1R), and stimulation of vagal C fibers via receptors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of ticagrelor-related dyspnea was the same in both patients with chronic heart failure or chronic obstructive pulmonary disease and those without these diseases [31]. Up to date, the two most plausible hypotheses explaining the potential mechanisms of ticagrelor-induced dyspnea have been debated [10,32]. In the literature, the greatest attention is paid to a structural similarity between ticagrelor and adenosine, activation of adenosine receptors (A1R), and stimulation of vagal C fibers via receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors state that ticagrelor can induce dyspnea via P2Y12 receptors present on vagal C fibers themselves. Some literature sources mention the third cause of dyspnea, i.e., ticagrelor-induced release of adenosine triphosphate (ATP) from erythrocytes; however, this hypothesis is less plausible (Figure 1) [10,32]. The most plausible hypotheses explaining the causes for the occurrence of ticagrelorrelated dyspnea are as follows [10,32]:…”
Section: Introductionmentioning
confidence: 99%
“…Across the lungs, there are no pathological auscultatory characteristics, although severe bronchial spasms with a reduction in blood oxygen may be found. Dyspnea attacks frequently recur over the course of a few hours or even days [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bradycardia and blocks in the conduction system arise approximately two hours after taking the medication, last for a short time, and then disappear; in most cases, they do not manifest clinically [ 9 ]. The most frequent type of bradyarrhythmia is sinus bradycardia (39.6%), followed by dropped beats (31.2%) and then ventricular pauses (5.8%) predominantly due to AV node pauses and secondarily due to AV blocks [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although ticagrelor is generally well tolerated [ 41 ], dyspnea which is mild to moderate in severity was observed in premarketing studies [ 42 , 43 ]. Dyspnea, related to ticagrelor therapy mainly develops shortly after the first days of treatment and has been linked to the increased extracellular level of adenosine [ 44 ]. In the present trial, early onset of dyspnea cases was reported only in the brand Brilique®.…”
Section: Discussionmentioning
confidence: 99%